Exploration vs. acquisition of oil and gas reserves: Effect on stock returns - Bård Misund; Bin Li (Cogent Economics & Finance, 2018)
This paper examines how oil and gas companies' reserves growth affects their share price returns. In particular we examine three issues affecting the relation between reserves changes and oil and gas firm returns. First, we examine if investors value reserves replacement as a result of exploration activities differently to reserves growth through acquisitions. In the second analysis, we test if reserves replacement of oil reserves impacts stock returns differently than changes in gas reserves do. Third, we examine the impact of the Shale gas revolution and the subsequent oil and gas price divergence on the association between returns and replacement of oil versus gas reserves. The results suggest that investors seem to be indifferent to reserves replacement strategy (exploration or acquisition). However, we find that changes in oil reserves impact oil and gas company returns differently than changes in gas reserves does. Moreover, we find that there has been a structural shift in the relation between returns and changes in gas reserves (but not changes in oil reserves) after 2008, coinciding with the Shale gas revolution and the break in the oil-gas price link. This latter result can be relevant for understanding the impact of the recent fall in oil prices on investor valuation of oil and gas reserves.
Keywords: 330; oil and gas reserves; reserves replacement; stock returns; acquisition; oil company; oil and gas company; exploration